1980
DOI: 10.1111/j.1432-1033.1980.tb06059.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase‐3 from Rabbit Skeletal Muscle

Abstract: 1. A glycogen synthase kinase was partially purified from rabbit skeletal muscle by precipitation with ammonium sulphate, chromatography on DEAE-cellulose and chromatography on hydroxyapatite.2. The enzyme was highly specific for glycogen synthase. In the standard assay, the relative rates of phosphorylation were : glycogen synthase (loo), phosvitin (2.5), phosphorylase kinase ( < l), casein (0.3), protein phosphatase inhibitor-I (< ().I), phosphorylase (< 0.01), mixed histones (< 0.01). The enzyme was separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
120
0
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 769 publications
(122 citation statements)
references
References 35 publications
0
120
0
2
Order By: Relevance
“…Nonphosphorylated GSK3␤ is constitutively active and represses glycogen synthase activity (28). Importantly, GW4064 treatment of db͞db mice increased the hepatic levels of phosphorylated GSK3␤ (at Ser-9) (Fig.…”
Section: Gw4064 Increases Hepatic Glycogen Synthesis and Storage In Dmentioning
confidence: 99%
“…Nonphosphorylated GSK3␤ is constitutively active and represses glycogen synthase activity (28). Importantly, GW4064 treatment of db͞db mice increased the hepatic levels of phosphorylated GSK3␤ (at Ser-9) (Fig.…”
Section: Gw4064 Increases Hepatic Glycogen Synthesis and Storage In Dmentioning
confidence: 99%
“…Notably, Thr 60 in UNG2 conforms to a consensus sequence for GSK-3 (Ser/Thr-XXX-Ser(P)/Thr(P)) when Ser 64 is phosphorylated. Originally identified in 1980 (29), GSK-3 has since been shown to phosphorylate nearly 100 substrates (28) and influence many distinct cellular processes, including metabolism, proliferation (30), differentiation (27), and cancer progression (31)(32)(33)(34)(35)(36).…”
Section: Uracil N-glycosylase (Ung)mentioning
confidence: 99%
“…The protein kinase GSK-3 2 is ubiquitously expressed, and, although it was originally identified as a suppressor of glycogen synthase (6), GSK-3 has been implicated in a myriad of metabolic and signaling pathways (7). Recent studies have identified GSK-3␤ as a negative regulator of both cardiac and skeletal muscle hypertrophy (8,9) as well as muscle differentiation (10).…”
mentioning
confidence: 99%